PENGARUH RETURN ON ASSETS (ROA) TERHADAP NILAI PERUSAHAAN DENGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN GOOD CORPORATE GOVERNANCE (GCG) SEBAGAI VARIABEL MODERASI (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PADA TAHUN 2014-2018) - Wahid, Ardila Hi; Bailusy, Muhsin N (Jurnal MS, 2020)
Objective: This research aims to know and analyze the influence of Return On Asset(ROA) to the company’s value with the disclosure of Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG) as moderation variables (case studies on Manufakturing Companies listed on the indonesia Stock Exchange (IDX) Period (2014-2018). Samples in this study used the purposive sampling method. Based on the selection of samples according to the criteria specified, the number of samples in this study was as much as 20 companies or as many as 100 observation units in a 5 year period. Methodology: The analytical methods used in this study were two namely multiple regression analyses and moderated regression analysis. Finding: H1 and H2, are accepted, but H3 no accepted at the 5% confidence level. Conclusion: The results showed that Return On Asset (ROA) positively impacted the value of the company. The greater the value of ROA, showing the better performance of the company, because the rate of return on investment is greater. However, CSR as a moderation variable is not able to moderate the influence of Return On Asset (ROA), The value of the company. The low of the pilot is because the shareholders or stakeholders focus more on the company's performance or focus solely on the amount of profit generated. GCG as a moderation variable is unable to moderate the influence of Return On Asset (ROA) on the company's value Due to the percentage of shares ownership by managers are still very small constraints in optimizing the GCG mechanism within the company.